The International Kâtip Chalabi Symposium (American Journal of Islam and Society, 2015)
The Constantinople-born Mustafa bin Abdullah Kâtip Chalabi (popularlyknown as Haji Khalifa [1609–57]) was one of the most notable Muslim scholarsof his time. Kâtip Chalabi, as he is known as in Turkish circles, was a reformistscholar known for his intellectual contributions to the social sciences(viz., [Ottoman] history, geography, and economics) and his invaluable biobibliographicaltext Kashf al-Zunūn, which contains over 14,000 entries. Heis generally considered as one of Ottoman Turkey’s most productive authors,for his writings provided an invaluable input to “the classification of knowledge”systems. For this reason, the Istanbul Foundation for Research and Education(ISAR; http://isar.academia.edu), the Turkish Centre for IslamicStudies (ISAM; http://english.isam.org), and the Cairo-based Institute of ArabicManuscripts (MSC; www.manuscriptcenter.org) decided to co-host aMarch 6-8, 2015, symposium to celebrate and address his contributions.The joint Committee for the International Kâtip Chalabi Symposiumchose “Bibliography and the Classification of Knowledge in Islamic Civilization”as its main theme and set numerous goals, among them to (a) raise basicissues related to the Islamic classification of knowledge and bibliography, (b)reveal how this tradition can be reconsidered with respect to the discipline ofbibliography, which has shifted into a new phase due to theoretical and practicaldevelopments in today’s world; (c) provide the necessary basis for discussinghis scholarly achievements; and (d) offer foundations for futureresearch that would build upon his bibliographic encyclopedia Kashf al-Zunūn‘an Asāmī al-Kutub wa al-Funūn (The Removal of Doubt from the Names ofBooks and the Arts).Since it is beyond the scope of this brief report to comment on each presentation,most of which were delivered in Arabic and Turkish with simultaneoustranslations, I have decided to provide a general overview of a selectionof papers from each thematic session.Ahmad Shawqi Benbin (Al-Khazanat al-Malakiyyah al-Hasaniyyah, Morocco),one of the first speakers, addressed “Kashf al- Zunūn and InternationalBibliography,” which related directly to the symposium’s general theme of“Kâtip Chelebi: Philosophy of the Sciences of Bibliography and Classification.”While offering a historical context within which to view Chalabi’s intellectualoutput, he traced the science of bibliography back to Abu al-Faraj ...